O ensino de música para alunos cegos em classe regular de ensino no Colégio Universitário da UFMA - Rocha, Eliza de Oliveira (2016)
This research intends to present a musical-pedagogical work with blind students in the regular classes of the educational system in the Enforcement school of the Federal University of Maranhão - COLUN/UFMA. Therefore, it will bring the main international and national laws and documents that treat the education as a right of all, since 1945, when was created the ONU, until nowadays, which have influence in the daily teaching labor. It will also contextualize, historically, the music teaching trajectory and the universal feature that it has taken during the 20th century and beginning of the present century. And finally, it will make a musical-pedagogical experience which was developed in COLUN/UFMA with the the blind and non-blind students in the regular classes of the educational system as a music workshop. In this context, we intend to answer the following problem “How can we teach music for the blind students of the regular classes in COLUN/UFMA?”. In an analitic-descritive, and qualitative approach, this research uses the search-action modality. The date of this research were colected in field survey, through direct personal observation, record of the classes gotten by reports, pictures, audio and video records and semi-structured interviews searching for a feedback from the students about the focused proposal. It was shown by the results that, the teachers need to know the legal references about the education for all, and the innovations discovered in the musical-pedagogy in order to draw a methodological way that can be executed in a manifold context, which the referrals must be flexile and reach all the students.